2009
DOI: 10.2746/042516409x424162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise and joint topography on depth‐related spatial distribution of proteoglycan and collagen content in immature equine articular cartilage

Abstract: This study confirms earlier observations that even moderate variations in exercise level in early age may have significant effects on the collagen network of articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Although no significant differences were observed between controls and runners in OA grades of the oldest age group, it is possible that the observed exercise-induced decrease in amide I content in the superficial zone and the increase in the deep2 zone relate to tissue degradation. Earlier, Brama et al [53] reported that a slight increase in exercise of maturing horses could lead to a decrease in the amide I content in a load-bearing area. Although we failed to detect any significant decrease in the amide I content in the earlier age groups, a similar trend was apparent below the superficial zone ( Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…Although no significant differences were observed between controls and runners in OA grades of the oldest age group, it is possible that the observed exercise-induced decrease in amide I content in the superficial zone and the increase in the deep2 zone relate to tissue degradation. Earlier, Brama et al [53] reported that a slight increase in exercise of maturing horses could lead to a decrease in the amide I content in a load-bearing area. Although we failed to detect any significant decrease in the amide I content in the earlier age groups, a similar trend was apparent below the superficial zone ( Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…The composition of subchondral bone is uniquely designed to disperse axial loads across the joint, sparing the overlying articular cartilage (58). Subchondral bone has the innate ability to display a range of responses, reflecting both acute stresses as well as more prolonged, chronic, adaptive responses within the joint.…”
Section: Anatomy and Physiology Of Subchondral Bonementioning
confidence: 99%
“…Many studies use FT-IR imaging spectroscopy (FT-IRIS), a technique which couples an FT-IR spectrometer to an array detector and an optical microscope, thus allowing mapping of specific molecules in the tissue at high pixel resolution within a defined region of interest. 4, 6, 7, 10, 11, 13, 26, 29, 30, 45, 46 An additional advantage of FT-IR is the coupling of an infrared fiber optic probe (IFOP) to an FTIR spectrometer. This device provides spectral acquisition from intact tissues in situ, with the potential for in vivo assessments.…”
Section: Introductionmentioning
confidence: 99%